Recent Advances in the Development of Indazole‐based Anticancer Agents. (26th June 2018) - Dong, Jinyun; Zhang, Qijing; Wang, Zengtao; Huang, Guang; Li, Shaoshun
Abstract: Cancer is one of the leading causes of human mortality globally; therefore, intensive efforts have been made to seek new active drugs with improved anticancer efficacy. Indazole‐containing derivatives are endowed with a broad range of biological properties, including anti‐inflammatory, antimicrobial, anti‐HIV, antihypertensive, and anticancer activities. In recent years, the development of anticancer drugs has given rise to a wide range of indazole derivatives, some of which exhibit outstanding activity against various tumor types. The aim of this review is to outline recent developments concerning the anticancer activity of indazole derivatives, as well as to summarize the design strategies and structure–activity relationships of these compounds. Abstract : Indazole innovation : Pharmacologically diverse 1 H ‐ and 2 H ‐indazole analogues exert their antineoplastic activities through the inhibition of receptor tyrosine kinases (RTKs), serine/threonine kinases, and transcription factors, or by killing cells directly by forming cytotoxic metal‐based complexes. This review outlines recent developments in the anticancer activity of indazole derivatives and summarizes design strategies and structure–activity relationships.